MEDIUM TERM OUTCOME FOR A CONSTRAINED ACETABULAR COMPONENT AT A SINGLE INSTITUTION: WHAT IS IMPORTANT FOR SUCCESS? - Tayton, Edward; Elliott, Robert; Butt, Faisal Farooq; Farrington, William; Sharp, Robert (Journal of Ayub Medical College Abbottabad, 2019)
Background: The use of constrained Total Hip Replacements (THR) is controversial due to lack of definite indications and potentially high failure rates because of mechanical loosening or component failure. A review was performed to assess a departmental use of a single constrained acetabular component over a ten years period. Methods: Patient demographics, operative indications, complications and patient follow-up were recorded. Post-operative Oxford Hip Scores (OHS) were obtained via a combination of New Zealand Joint Registry interrogation and telephonic questioning. Cup version and inclination angles were obtained from standardised anteroposterior radiographs using established techniques. Results: Forty-four constrained components (in 39 patients) were implanted between 2005 and 2014. The mean age was 78 years with mean ASA 2.7 and mean follow-up 37.2 months (range 13-116). The mean post-operative OHS was 36 (SD 9.25), and there were 4 failures (3 dislocations and 1 peri-prosthetic fracture). The 3 dislocations had either cup ante version (AV) or inclination angles (IA) outside the data set interquartile range (AV 13-24°, IA 40-50°). The cup inclination was significantly lower (p<0.01) in patients with pain on sitting. At post-operative follow-up, 14/39 patients had died from unrelated causes, with only 1 patient surviving beyond 6 years. Conclusions: Constrained acetabular components offer a solution to hip instability in a difficult group of patients. This study has shown good medium-term outcomes of a single component type in a predominantly frail group of low demand patients. Despite constraint, correct cup placement (particularly inclination) remains important to prevent dislocation or poor reported outcome. Keywords: Acetabulum; Constrained; Inclination; Medium term; Outcome